2010
DOI: 10.1089/acm.2009.0502
|View full text |Cite
|
Sign up to set email alerts
|

Resident-Initiated Integrative Medicine Curriculum in an Allopathic Family Medicine Residency

Abstract: For residents with interest in integrative medicine, weekly resident-run teaching sessions support their personal and professional growth and may improve their overall spirit during residency. In residency programs with limited teaching in integrative medicine, residents can successfully take initiative and create their own curriculum with support from community providers and interested faculty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
1
Order By: Relevance
“…Research has shown that physicians feel they do not have enough familiarity and knowledge of CAM and that further education is necessary for integration of CAM into their practices. 28,29 Increasing such knowledge may result in greater usage of alternative treatment plans to supplement conventional medicine and improve outcomes for secondary complications associated with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that physicians feel they do not have enough familiarity and knowledge of CAM and that further education is necessary for integration of CAM into their practices. 28,29 Increasing such knowledge may result in greater usage of alternative treatment plans to supplement conventional medicine and improve outcomes for secondary complications associated with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support multiple other studies that have illustrated healthcare provider interest in CAM, as well as the necessity for providers to become educated about alternative medicine. [28][29][30][31] Increasing education and awareness regarding CAM practices may result in a greater number of healthcare professionals and laypersons recommending and inquiring about its use.…”
Section: Discussionmentioning
confidence: 99%
“…8,19 There are several examples in the literature of successful implementation of curriculum by motivated residents and residencies open to CAM/IM. 7,20 …”
Section: Discussionmentioning
confidence: 99%
“…Flannery és mtsai úgy találták egy 2006-ban megjelent felmérés-ben, hogy a családorvosok 70%-a érdeklődik a nem-konvencionális gyógymódok iránt [10]. Laudenberg és mtsai szerint azonban nemcsak a szakorvosok, hanem a frissen végzett orvosok is érdeklődnek a nem-konvencionális gyógymódok alkalmazása iránt [11]. Családorvos-rezidensek között végzett felmérésük szerint a rezidensek nemcsak érdeklődnek az integratív medicina iránt, hanem örömmel vennék ezek oktatását is, mivel jó lehető-ségnek tartják az ilyen jellegű tanfolyamokat személyes és szakmai fejlődésre egyaránt.…”
Section: Megbeszélésunclassified